Diagnosis and management of a full thickness macular hole - Fontaine, Nicolas; Olivier, Sébastien (Canadian Journal of Optometry, 2012)
Background: First stage macular holes are not always easily identified without the use of medical imagery. Differential diagnosis from other macular conditions is possible with a keen eye and the use of a binocular fundus lens. However, the advent of optical coherence tomography facilitates accurate diagnosis. Case Report: This report demonstrates a classical case of a full thickness macular hole. The clinical signs are not pathognomonic at first, but typical signs develop in the following weeks. The different stages of the disease are described, as well as current state of surgical treatment and possible outcomes. Conclusions: Early diagnosis allows quick visual recovery. Nevertheless, this condition can be treated up to one year after occurrence with significant improvement of visual function.